1986
DOI: 10.1002/mds.870010107
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral blepharospasm and contralateral hemidystonia and parkinsonism in a patient with a unilateral rostral brainstem– thalamic lesion: Structural and functional abnormalities studied with CT, MRI, and PET scanning

Abstract: A patient developed progressive right hemidystonia in childhood. Subsequently, left-sided blepharospasm, slurred and stuttering speech, and right-sided rigidity and bradykinesia, responsive to dopamine agonists, appeared. Investigation with computed tomography and magnetic resonance imaging (MRI) at age 43 years revealed a left-sided calcified rostral brainstem-thalamic lesion of uncertain aetiology. Although no structural lesion was seen in the striatal regions, L-[18F]-fluorodopa uptake was severely diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Leenders et al proposed that the delayed development of dystonia may be related to "slowly evolving" aberrant neuronal sprouting. 58 In our review, the latency was longest when hemidystonia was secondary to perinatal injury. This may be related to the greater ability of the developing brain to recover from cerebral insults, or secondary to a delayed recognition of this syndrome in young children.…”
Section: Discussionmentioning
confidence: 70%
“…Leenders et al proposed that the delayed development of dystonia may be related to "slowly evolving" aberrant neuronal sprouting. 58 In our review, the latency was longest when hemidystonia was secondary to perinatal injury. This may be related to the greater ability of the developing brain to recover from cerebral insults, or secondary to a delayed recognition of this syndrome in young children.…”
Section: Discussionmentioning
confidence: 70%
“…These lesion data do not demonstrate that any one brain region is more likely involved in the acquisition of stuttering. Many of the more recent studies, which used neuroimaging, reported involvement of the basal ganglia, with the putamen being listed most often (Abe, Yokoyama, & Yorifji, 1992;Andy & Bhatnagar, 1991;Carluer et al, 2000;Ciabarra, Elkind, Roberts, & Marshall, 2000;Heuer, Sataloff, Mandel, & Travers, 1996;Kono, Hirano, Ueda, & Nakajima, 1998;Lebrun, Leleux, & Retif, 1987;Leenders et al, 1986;Ludlow et al, 1987;Shibuya, Wakayama, Murahashi, Aoki, & Ozasa, 1998). A few other studies have reported injuries involving the corpus callosum (Hagiwara, Takeda, Saito, Shimizu, & Bando, 2000;Soroker, Bar-Israel, Schechter, & Solzi, 1990;Tsumoto, Nishioka, Nakakita, Hayashi, & Maeshima, 1999).…”
Section: Location Of Brain Injury That Induces Speech Dysfluencymentioning
confidence: 95%
“…Blepharospasm may occur in diseases of the basal ganglia or in association with upper brain stem abnormalities. [1][2][3][4][5][6][7][8] In most patients, however, it is idiopathic in origin.…”
mentioning
confidence: 99%